International workers' educational supplement
Suppl. to: Press réports of the International Federation of Trade Unions (ZK 16042). - Continues: International educational notes (ZK 16042). - French ed.: Informations internationales d'éducation ouvrière (ZK 16040). - Dutch ed.: Internationale arbeidersonwikkeling (ZK 16038). - German ed.: Mitteilungen über das internationale Arbeiterbildungswesen (ZK 16157).